Effect of varietal attributes on the adoption of an orange-fleshed sweetpotato variety in Upper East and Northern Ghana - Adekambi, S.; Okello, J.J.; Rajendran, S.; Acheremu, K.; Carey, E.E.; Low, Jan W.; Abidin, P.E. (SAGE Publications, 2020)
Despite sustained economic growth and reduction in some of forms of malnutrition, Ghana still faces a national prevalence rate of 20.8% vitamin A deficiency (VAD) among for children 6–59 months old. Orange-fleshed sweetpotato (Ipomoea batatas L.) (OFSP) can significantly improve vitamin A intake and contribute toward reducing VAD, especially in Northern Ghana where VAD is 31% among young children. Several poverty and nutrition projects in Ghana have promoted the use of OFSP for its health benefits. This study assesses the effect of three varietial attributes on adoption of the first released OFSP variety in Northern Ghana namely, Apomuden. The study concluded that sweetness, taste and dry matter have joint significant effects on adoption of an OFSP variety. The positive and negative traits highlighted will inform the on-going breeding effort.